Podredumbres basales de Gypsophila paniculata (Caryophyllaceae): Agentes causales y su patogenicidad potencial sobre Dianthus caryophyllus (Caryophyllaceae) - Wolcan, Silvia María (2007)
The aims of the paper were to determine the causal agents of basal rots of Gypsophila paniculata in Argentina, and to evaluate its possible pathogenicity on Dianthus caryophyllus. Fusarium solani, F. oxysporum, Phytophthora nicotianae, Rhizoctonia solani, F. graminearum, F. verticilloides, F. equiseti and Pythium sp. were isolated in decreasing order from plants with symptoms of «crown rot» (the major basal rot). F. graminearum, F. oxysporum and F. solani were isolated from plants with «basal stem rot». Inoculations of gypsophila were performed by soil infestation and by placing inoculum on basal stem wounds with different strains of each fungus. Crown rot was incited by P. nicotianae causing fast decay of leaves and stems and wet soft rot of the crowns, and by R. solani causing slower decay and disintegrated crown tissues. Basal stem rot was incited by F. graminearum, which was described for the first time on G. paniculata and enter through wounded tissues. Under experimental conditions some strains of R. solani and F. graminearum isolated from gipsofila caused stem rot on carnation plants and only some strains of P. niconianae were weakly pathogenic.